Does Resilience Affect Students’ Psychological Distress in Indonesia? A Meta-Analysis Study - Manullang, Nurhamidah; Jailani, Jailani; Sulistyowati, Endang; Hafidz, Sholeh; Handaru, Calista Devi (FKIP Universitas Lampung, 2024)
Abstract: Does Resilience Affect Students' Psychological Distress in Indonesia? A Meta-Analysis Study. Objectives: This research aims to assess the influence of resilience on the formation of psychological distress among students in Indonesia as a whole. Methods: The method used for the purposes of this research is correlational meta-analysis by analyzing 10 primary studies with a sample size (N = 3600), which meet the specified inclusion criteria. Findings: The results of the analysis using the random-effects approach obtained a combined effect size of (g = 0.614; p < 0.01). This effect size is in the “Medium Effect” category. Conclusion: Overall, resilience has a significant effect on the psychological distress of students in Indonesia. The findings of this meta-analysis can provide more accurate and reliable conclusions than single studies. Apart from that, this study can also be a consideration and solution in overcoming the problem of psychological distress in an academic context. Keywords: psychological distress, resilience, meta-analysis.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202412